The Discourse of Christianity in Viktor Orbán’s Rhetoric - Máté-Tóth András; Rakovics Zsófia (2023)
This paper studies the views of Hungary’s Prime Minister Viktor Orbán on religion and Christianity, using both quantitative and qualitative methods. The analysis is based on Viktor Orbán’s speeches in Băile Tușnad, at Bálványos Free Summer University and Student Camp (commonly known as Tusványos), which are suitable to sensitively trace the evolution of his thinking from 1990 to 2022. The analysis shows how the concept of Christianity has changed in meaning in the speeches, how it has been linked to political issues, and in what ways Orbán’s thinking has been similar to and different from political Christianity and religious Christianity. Orbán’s concept of Christianity can be understood within the theoretical framework of populism developed by Ernesto Laclau and Chantal Mouffe: in the discursive struggle for political hegemony, there is a continuous construction of ‘the people’, of society, in which ‘empty markers’ play a key role. Orbán’s concept of Christianity can thus be adequately interpreted in terms of the discourse of the permanent creation of the ‘nation’. The political emphasis on Christianity is related to the wounded collective identity of Hungarian society. The paper argues that because of the collective woundedness, society requires an overarching narrative symbolizing unity, of which Christianity is a key concept.
Keywords: Filozófia, etika és vallástudományok